Highway To Happiness - Abejo, Bisi (Longman Nigeria Plc, 1996)
When Seyi Sofunde discovered that his new engineer,Taiwo Williams,was a woman,he thought his boss who gave her the job must be suffering from a Senile decay.
Keywords: Fiction-Romance